Ionic Conductive Organohydrogel With Ultrastretchability, Self-Healable and Freezing-Tolerant Properties for Wearable Strain Sensor - Ji, Feng; Jiang, Min; Yu, Qingyu; Hao, Xuefang; Zhang, Yan; Zhu, Junqiu; Luo, Shuiyuan; Li, Junjie (Frontiers in Chemistry, 2021)
Currently, stretchable hydrogel has attracted great attention in the field of wearable flexible sensors. However, fabricating flexible hydrogel sensor simultaneously with superstretchability, high mechanical strength, remarkable self-healing ability, excellent anti-freezing and sensing features via a facile method remains a huge challenge. Herein, a fully physically linked poly(hydroxyethyl acrylamide)-gelatin-glycerol-lithium chloride (PHEAA-GE-Gl-LiCl) double network organohydrogel is prepared via a simple one-pot heating-cooling-photopolymerization method. The prepared PHEAA-GE-Gl-LiCl organohydrogel exhibits favorable stretchability (970%) and remarkable self-healing property. Meanwhile, due to the presence of glycerol and LiCl, the PHEAA-GE-Gl-LiCl organohydrogel possesses outstanding anti-freezing capability, it can maintain excellent stretchability (608%) and conductivity (0.102 S/m) even at −40°C. In addition, the PHEAA-GE-Gl-LiCl organohydrogel-based strain sensor is capable of repeatedly and stably detecting and monitoring both large-scale human motions and subtle physiological signals in a wide temperature range (from −40°C to 25°C). More importantly, the PHEAA-GE-Gl-LiCl organohydrogel-based sensor displays excellent strain sensitivity (GF = 13.16 at 500% strain), fast response time (300 ms), and outstanding repeatability. Based on these super characteristics, it is envisioned that PHEAA-GE-Gl-LiCl organohydrogel holds promising potentials as wearable strain sensor.